Succinct Palette and Color Model Generation and Manipulation Using Hierarchical Representation - Jeong, Taehong; Yang, Myunghyun; Shin, Hyun Joon (Computer Graphics Forum, 2019)
We propose a new method to obtain the representative colors and their distributions of an image. Our intuition is that it is possible to derive the global model from the local distributions. Beginning by sampling pure colors, we build a hierarchical representation of colors in the image via a bottom-up approach. From the resulting hierarchy, we can obtain satisfactory palettes/color models automatically without a predefined size. Furthermore, we provide interactive operations to manipulate the results which allow the users to reflect their intention directly. In our experiment, we show that the proposed method produces more succinct results that faithfully represent all the colors in the image with an appropriate number of components. We also show that the proposed interactive approach can improve the results of applications such as recoloring and soft segmentation.
Keywords: Bottom up approach; CCS Concepts; Hierarchical representation; Image manipulation; Interactive approach; Interactive operations; Local distributions; Number of components; CCS Concepts; Hierarchical representations; • Computing methodologies → Image manipulation